Humanising mobile online ESL blended learning model - Mohamad Noor, Mohd Yusri; Tengku Sharif, Tengku Intan Suzila; Omar, Siti Rohana; Teo, Kok Seong (Universiti Sultan Zainal Abidin, Malaysia, 2022)
Background and Purpose: The COVID-19 pandemic has given a massive proliferation of technology, particularly in education, redefining language learning from face-to-face (F2F) and off-classroom known as blended learning (BL) to a new kind in online distance learning/education (ODL/E). BL is now a mix of synchronous and asynchronous learning. The shift, however impressive it may appear, does not guarantee the effectiveness of the learning process. The gap that leads to the current study is how bibliometrics has shown minimal focus on undergraduates’ acceptance of these changes, especially in English as a Second Language (ESL) learning classes to the newly embraced online BL (OBL) and how humanistic values are important in ESL lessons. Thus the study sets out to understand several issues pertaining to the use of mobile communication devices as a learning tool in ESL MoBL. Methodology: The present study is a mixed-method research approach using a sequential exploratory design. A set of Technology Acceptance Model (TAM) questionnaires was distributed to understand 264 teacher-trainers, degree and diploma students’ inclination towards ESL mobile learning platforms after a semester of mobile open blended learning (MoBL) integration, whilst side-lining the unnecessary information of Unified Theory of Acceptance and Use of Technology (UTAUT2). Interviews based on Analysis, Design, Assess, and Belief (ADAB) Model further enriched the data on the humanisation aspects of MoBL. Findings: Findings showed that learners’ inclination to the new MoBL can be affected by gender, age, and maturity. Thus to implement a more humanistic learning modification demands a thorough understanding of students’ needs. Contributions: The novelty of these findings is the sampling contrasting both degree and diploma students along with teacher-trainees’ perceptions of humanistic values in OBL highlights the effects of, age, maturity and gender on technology in education. This paper suggests a discussion on the humanistic MoBL model for ESL learners. The future implication of the findings suggests age, maturity, and gender affect students’ inclination towards the new MoBL, and pushes the need for more humanistic essences in MoBL.